Hybrid Mold: Comparative Study of Rapid and Hard Tooling for Injection Molding Application Using Metal Epoxy Composite (MEC) - Radhwan Hussin (Materials, 2021)
The mold-making industry is currently facing several challenges, including new competitors in the market as well as the increasing demand for a low volume of precision moldings. The purpose of this research is to appraise a new formulation of Metal Epoxy Composite (MEC) materials as a mold insert. The fabrication of mold inserts using MEC provided commercial opportunities and an alternative rapid tooling method for injection molding application. It is hypothesized that the addition of filler particles such as brass and copper powders would be able to further increase mold performance such as compression strength and thermal properties, which are essential in the production of plastic parts for the new product development. This study involved four phases, which are epoxy matrix design, material properties characterization, mold design, and finally the fabrication of the mold insert. Epoxy resins filled with brass (EB) and copper (EC) powders were mixed separately into 10 wt% until 30 wt% of the mass composition ratio. Control factors such as degassing time, curing temperature, and mixing time to increase physical and mechanical properties were optimized using the Response Surface Method (RSM). The study provided optimum parameters for mixing epoxy resin with fillers, where the degassing time was found to be the critical factor with 35.91%, followed by curing temperature with 3.53% and mixing time with 2.08%. The mold inserts were fabricated for EB and EC at 30 wt% based on the optimization outcome from RSM and statistical ANOVA results. It was also revealed that the EC mold insert offers better cycle time compared to EB mold insert material.